The Critical Blood Bank’s Inventory Management Improvement Using Information System Through the Implementation of Internet of Things - K. M. Rustan, M. Dachyar (International Journal of Advanced Science and Technology, 2020)
Blood Stockout cases are a common occurrence in Indonesian Hospitals. It is crucialespecially in an emergency situation, where the delay process of blood replenishment anddistribution could cause death to the patient. The problem of blood replenishment anddistribution is caused by the time inefficiency or manual data communication amongHospitals and Indonesian Red Cross. The purpose of this research is to design processimprovement of hospital blood bank’s inventory management through an informationsystem and the utilization of Internet of Things. Business Process Reengineeringapproach was used to show the process improvement of management inventory inHospital Blood Bank (HBB). The method in this study is information system developmentwith entity relationship diagram (ERD), relational database, use case diagram, and dataflow diagram (DFD). The results have five scenarios of process improvement. The bestscenario could increase the efficiency of process time by 75.63%, which previously took7.14 hours to 1.74 hours.